Parastenocarididae (Crustacea, Copepoda, Harpacticoida) of India: description of Parastenocaris mahanadi n. sp., and redescription of P. curvispinus Enckell, 1970 from hyporheic habitats - Reddy, Yenumula Ranga; Defaye, Danielle (Zootaxa, 2007)
Only four species of the genus Parastenocaris Kessler, 1913, were previously known from India: P. curvispinus Enckell, 1970, P. gayatri Ranga Reddy, 2001, P. savita Ranga Reddy, 2001, and P. sandhya Ranga Reddy, 2001. A fifth species, Parastenocaris mahanadi n. sp., is here described from the hyporheic habitat of the River Mahanadi near Raipur city in the State of Chhatisgarh, central India. This is the first Indian representative of the minuta species-group. It can be distinguished from the other members of this group by a unique combination of morphological characters, especially of the male: fifth antennular segment bearing an extraordinarily long aesthetasc and seventh segment without apophysis; caudal rami as long as anal somite and over four times as long as their maximum width; lateral setae inserted at about distal third of rami; anal operculum smooth; leg 4 bearing two chitinized, claw-like spines at distal inner corner of basis; endopodite small, 0.4 as long as first exopodite segment and ornamented with two groups of long spinules; leg 5 produced into smooth, slender, acute, spinous process at distal inner corner, and with only three setae. Parastenocaris curvispinus, which was originally incompletely described from Sri Lanka by Enckell (1970), is redescribed from several hyporheic habitats. This highly variable species, which was found co-occurring, inter alia, with P. mahanadi n. sp., is the dominant and most wide-spread parastenocaridid in the hyporheic habitats of peninsular India. Following the recent resurrection of the genus Remaneicaris Jakobi, 1972, the taxonomic position of this species is reviewed. Furthermore, the distribution of the Indian parastenocaridids is briefly discussed.